The role of emotional aspects in the information retrieval from the web. Issue 4 (30th July 2018) - Yari Zanganeh, Marzieh; Hariri, Nadjla
Abstract : Purpose: The purpose of this paper is to identify the role of emotional aspects in information retrieval of PhD students from the web. Design/methodology/approach: From the methodological perspective, the present study is experimental and the type of study is practical. The study population is PhD students of various fields of science. The study sample consists of 50 students as selected by the stratified purposive sampling method. The information aggregation is performed by observing the records of user's facial expressions, log file by Morae software, as well as pre-search and post-search questionnaire. The data analysis is performed by canonical correlation analysis. Findings: The findings showed that there was a significant relationship between emotional expressions and searchers' individual characteristics. Searchers satisfaction of results, frequency internet search, experience of search, interest in the search task and familiarity with similar searches were correlated with the increased happy emotion. The examination of user's emotions during searching performance showed that users with happiness emotion dedicated much time in searching and viewing of search solutions. More internet addresses with more queries were used by happy participants; on the other hand, users with anger and disgust emotions had the lowest attempt in search performance to complete search process. Practical implications: The results imply that the information retrieval systems in the web should identify emotional expressions in a set of perceiving signs in human interaction with computer, similarity, face emotional states, searching and information retrieval from the web. Originality/value: The results explicit in the automatic identification of users' emotional expressions can enter new dimensions into their moderator and information retrieval systems on the web and can pave the way of design of emotional information retrieval systems for the successful retrieval of users of the network.